The elephant in the room silence and denial in everyday life - Zerubavel, Eviatar. (Oxford University Press, 2006)
The fable of the Emperor's New Clothes is a classic example of a conspiracy of silence, a situation where everyone refuses to acknowledge an obvious truth. But the denial of social realities -- whether incest, alcoholism, corruption, or even genocide -- is no fairy tale. In this book, the author sheds new light on the social and political underpinnings of silence and denial -- the keeping of "open secrets." The author shows that conspiracies of silence exist at every level of society, ranging from small groups to large corporations, from personal friendships to politics. Drawing on examples from newspapers and comedy shows to novels, children's stories, and film, the book travels back and forth across different levels of social life, and from everyday moments to large-scale historical events. At its core, the book helps us understand why we ignore truths that are known to all of us. The author shows how such conspiracies evolve, illuminating the social pressures that cause people to deny what is right before their eyes. We see how each conspirator's denial is symbiotically complemented by the others, and we learn that silence is usually more intense when there are more people conspiring -- and especially when there are significant power differences among them. He concludes by showing that the longer we ignore "elephants," the larger they loom in our minds, as each avoidance triggers an even greater spiral of denial. Social life in families, organizations, communities and even entire nations is full of situations where the emperor has no clothes. The book illuminates the dynamics behind these situations, revealing why we ignore obvious and alarming realities.